2022
DOI: 10.3390/horticulturae8070572
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid Applications Enhance the Tolerance to Abiotic Stresses, Production and Quality of Strawberry Fruits

Abstract: Brassinosteriods (BRs) have increasingly been used to improve the yields and quality of various crops. In this work we studied the effect of two brassinosteroids, BB16 and EP24, on the growth promotion of Fragaria ananassa plants under normal conditions or exposed to water or saline stress. The influence of both BRs on the plant development and fruit quality was evaluated when cultivated in semi-hydroponic conditions. A marked growth-promoting effect was observed with both compounds when plants were cultivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Polyhydroxy steroids phytohormones, such as brassinosteroids, can also be used to improve crop salt tolerance [6,7]. Furio et al [7] found that strawberry treated with brassinosteroids was characterized by a higher shoot and root weight as well as a higher total weight of fruits per plant.…”
Section: Exogenous Compounds and Bioinoculants Increasing Stress Tole...mentioning
confidence: 99%
See 3 more Smart Citations
“…Polyhydroxy steroids phytohormones, such as brassinosteroids, can also be used to improve crop salt tolerance [6,7]. Furio et al [7] found that strawberry treated with brassinosteroids was characterized by a higher shoot and root weight as well as a higher total weight of fruits per plant.…”
Section: Exogenous Compounds and Bioinoculants Increasing Stress Tole...mentioning
confidence: 99%
“…Polyhydroxy steroids phytohormones, such as brassinosteroids, can also be used to improve crop salt tolerance [6,7]. Furio et al [7] found that strawberry treated with brassinosteroids was characterized by a higher shoot and root weight as well as a higher total weight of fruits per plant. Additionally, the quality of fruits obtained in salt stress conditions after brassinosteroids application was significantly higher than in non-treated individuals.…”
Section: Exogenous Compounds and Bioinoculants Increasing Stress Tole...mentioning
confidence: 99%
See 2 more Smart Citations
“…Two elicitors were obtained from strawberry leaves, the Fragarin [24] and the Ellagitanin HeT [25] and the elicitor Acremonium strictum Elicitor Subtilisin (AsES) that was purified from the avirulent fungus Acremonium strictum [26][27][28][29][30][31][32] . We have also investigated the two synthetic brassinosteroids (e.g., EP24 and BB16) with both plant defense and plant growth stimulation capacities [33][34][35] , and fungal-derived extracts, which are a complex mixture of elicitors-the latter may be comparable those vaccines made with whole inactivated pathogens [36,37] . Just to mention, we have also induced innate defenses in strawberry plants through a soft mechanical stimulus [38] , similar to what was previously observed by Benikhlef et al [39] in the model plant Arabidopsis thaliana.…”
Section: Immunization Agents and Types Of (Phyto) Vaccinesmentioning
confidence: 99%